Leadership Strategy for Equitable and Just Policing Education and Training at Valencia College, Orlando, Florida, U.S. - Goltz, Jeffrey (International Journal of Education Policy and Leadership, 2022)
In the summer of 2020, as social conflict polarized the United States and calls to reform and defund the police were heard across the nation, Valencia College stepped up and redefined its role to better serve students by taking steps to improve the training and education of the next generation of law enforcement and thereby to strengthen the community. A call to action by the college president to discuss adequate and inadequate law enforcement training and education led to engagement in deep conversations for solutions and fundamental change and efforts to be responsive and lead the training needs of local law enforcement agencies. To this end, the School of Public Safety adopted a holistic approach to seek solutions through a community, organizational, and administrative lens, based on the Public Affairs Triumvirate Leadership Strategy (Goltz, 2020). In this leadership strategy, three constructs with select approaches are grounded in traditional leadership ethics and dimensions. The strategy guided the School of Public Safety to the foundation and development of a collaborative strategic impact plan so Valencia College could aim to be an “agent of change” in the community by elevating equitable and just law enforcement education and training in central Florida. This endeavor also adopted a governance framework and Valencia College assembled a diverse thirty-member Equitable and Just Policing Education and Training Task Force to seek recommendations from the community. A theory of change, from a quantum perspective, grounded the recommendations from the Task Force to reframe law enforcement education and training at Valencia College, thus offering solutions in a turbulent environment. Solutions included changes to the law enforcement curriculum that are being assessed through equity minded learning outcomes, the adoption of a learning management system designed to enhance supplemental training in the law enforcement academy, a broadened equitable and just policing training strategy for officers and leaders in the field, deeper partnerships with criminal justice programs at regional high schools, and a leadership role in an ever-growing community resiliency group in central Florida.